2020
DOI: 10.1021/acsanm.0c01982
|View full text |Cite
|
Sign up to set email alerts
|

Pore Engineering of Covalently Connected Metal–Organic Framework Nanoparticle–Mixed-Matrix Membrane Composites for Molecular Separation

Abstract: Fine-tuning and pore environment control of covalently connected metal−organic framework (MOF) and mixed-matrix membrane (MMM) composite materials were achieved. Core−shell-type, dual-functionalized, zirconium-based MOFs were prepared through a postsynthetic ligand exchange (PSE) process, and active vinyl functionalities on the surface of MOF nanoparticles were utilized for polymerization by forming interfacial-covalent connections between MOF nanoparticles and polymeric membranes via thiol−ene click photopoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…The third functionalized MOF was the core–shell (CS)-type UiO-66-(NH 2 )/F 3 -CS, which was fabricated through a post-synthetic ligand exchange (PSE) process. ,, Simple treatment of UiO-66-NH 2 with 20 mol % of BDC-F 3 solution gave the F 3 -functionalized core–shell MOFs (10 mol % incorporation was confirmed by 1 H NMR, Figures S2–S4). The core–shell structure of these UiO-66 MOFs after the PSE treatment was confirmed several times through Raman mapping methods with large single crystals and sequential exchanges used in previous studies. Although it was carefully studied that the particle size could impact the PSE process and their distribution in the crystal by Ameloot and co-workers, the recent core–shell type UiO MOFs for size-selective catalysis have proved the effective core–shell structure from the PSE process with microcrystalline powder type MOFs and very similar PSE conditions . Since the present NH 2 -F 3 core–shell MOFs are too small for Raman mapping after cross-sectioning of a single crystal, both SEM-EDX (Scanning Electron Microscope Energy-Dispersive X-ray spectrometer) and TEM-EDX (Transmission Electron Microscope Energy-Dispersive X-ray spectrometer) were attempted to distinguish the ligand distributions on the surface with fluorine atoms (Figure S5).…”
Section: Results and Discussionsupporting
confidence: 57%
“…The third functionalized MOF was the core–shell (CS)-type UiO-66-(NH 2 )/F 3 -CS, which was fabricated through a post-synthetic ligand exchange (PSE) process. ,, Simple treatment of UiO-66-NH 2 with 20 mol % of BDC-F 3 solution gave the F 3 -functionalized core–shell MOFs (10 mol % incorporation was confirmed by 1 H NMR, Figures S2–S4). The core–shell structure of these UiO-66 MOFs after the PSE treatment was confirmed several times through Raman mapping methods with large single crystals and sequential exchanges used in previous studies. Although it was carefully studied that the particle size could impact the PSE process and their distribution in the crystal by Ameloot and co-workers, the recent core–shell type UiO MOFs for size-selective catalysis have proved the effective core–shell structure from the PSE process with microcrystalline powder type MOFs and very similar PSE conditions . Since the present NH 2 -F 3 core–shell MOFs are too small for Raman mapping after cross-sectioning of a single crystal, both SEM-EDX (Scanning Electron Microscope Energy-Dispersive X-ray spectrometer) and TEM-EDX (Transmission Electron Microscope Energy-Dispersive X-ray spectrometer) were attempted to distinguish the ligand distributions on the surface with fluorine atoms (Figure S5).…”
Section: Results and Discussionsupporting
confidence: 57%
“…Post-synthetic exchange (PSE) is an efficient synthetic approach for the preparation of improved MOFs through the replacement of building blocks in MOFs and is reported as a method to control the spatial distribution of building blocks 6 16 . During the process of exchanging building blocks, MOFs of uniform microstructures 17 22 and core–shell microstructures 23 30 were obtained as intermediate species. Matzger et al reported that the post-synthetic linker exchange of MOF-5 produces core–shell microstructural MOF crystals with different degrees of linker exchange and shell thicknesses depending on the types and molecular sizes of the solvents used 31 , 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Post-synthetic modification is another promising approach to modifying MOF particles toward better separation performances [ 90 , 91 , 92 , 93 , 94 ]. Al-Maythalony et al performed a linker exchange of benzimidazolate to benzotriazolate for ZIF-7 nanoparticles to tune the performance of ZIF-7/poly(ether imide) (PEI) membranes [ 95 ].…”
Section: Mixed-matrix Membranes For Hydrogen Separationmentioning
confidence: 99%